The Effect of Hospitalization on Older Couples - Donna Davis (EDIS)
“Very often the tale is told of an elderly couple for whom the loss of one spouse is more than the other can bear—and the other partner dies relatively soon thereafter. Referred to as the bereavement effect, this phenomenon has been well studied and documented. Likewise, research has explored the weighty effect that a spouse’s illness has on the caregiving partner, also called caregiver burden. Studies have shown that declines in physical and mental health of a spouse are often linked to a decrease in their partner’s health.” This 2-page Family Album Radio transcript was written by Donna Davis and published by the UF Department of Family, Youth and Community Sciences, August 2012.